Development of Student Worksheets (LKPD) With the Treffinger Learning Model to Improve Understanding and Creativity Learning Mathematics in High School Students - Nadrah Rangkuti, Ummi (EduMatika: Jurnal MIPA, 2022)
This development research aims to produce a product in the form of Student Worksheets (LKPD) with the Treffinger learning model on the material of valid criteria quadrilaterals and triangles. This study uses the Research and Development (R&D) development of the ADDIE model which includes five stages, namely analysis, design, product development or production, implementation, and evaluation. However, in the modification, this research only reached the implementation stage. The analysis stage is the stage of gathering information that can be used as material for making products consisting of curriculum analysis, concept analysis, and student analysis. The design stage is carried out by designing learning in the form of Student Worksheets and Learning Implementation Plans as well as data collection instruments in the form of validation sheets. In the development stage, instrument validation was carried out in the form of a questionnaire to the validator by media experts, material experts, and teachers. The results of this study produced Student Worksheets with the Treffinger learning model to improve students' understanding and creativity on valid quadrilateral and triangle material. Based on the results of the validator assessment questionnaire of the Student Worksheet, the value of the validation results by media experts is 80% in the valid category, material experts by 85% in the valid category, and the teacher by 82% in the valid category. As well as the Learning Implementation Plan obtained by 80% with a valid category. Finally, at the implementation stage, the results of the validation of student responses to the Student Worksheet with a percentage of 90% and fall into the very good category. The results of the final recapitulation of the assessment of students' conceptual understanding are 80% with high criteria. And the results of the analysis of students' creativity tests using n-gain is 0.64 in the medium category